CNC-C2: an ISO14649 and IEC61499 compliant controller - Harbs E.* (2021)
© 2021 Informa UK Limited, trading as Taylor & Francis Group.Manufacturing systems in the present industry must be flexible and allow fast reconfiguration to supply increasing demands for diversified products. Thus, a standard model for data exchange should be employed in a manner that the same data can be interpreted and used in different machines. In this work the ISO14649 (STEP-NC) standard is used to fulfil this requirement. Also, CNCs must be easily reprogrammable and able to reuse code for different tasks to reduce programming time. The contribution of this work is presenting a manufacturing system which is compliant to IEC 61499 and to STEP-NC, integrating them to fulfil requirements of interoperability and flexibility. A system, named CNC-C2, was developed (Computerised Numeric Control Compliant to STEP-NC and Compliant to IEC61499) with several software tools and integrated them to a machining hardware, also developed and presented in this paper. Experiments were performed in a test workpiece including STEP-NC compliant drilling, planar facing, linear and circular cutting features while using IEC61499 Function Blocks networks to perform the computational task. CNC-C2 achieved unprecedented interoperability and flexibility thanks to its compliance to Function Blocks and STEP-NC standards.